Total Quality Management Practices on Employees’ Job Involvement in Nepalese Manufacturing Industry (Pravaha, 2018)
The purpose of this paper is to examine the impact of total quality management practices on employees’ job involvement in Nepalese manufacturing industry. Structural questionnaire are used. Data was analyzed by employing correlation and sample regression analysis. The result of this study revealed that customer focus, training and education, teamwork, and organizational culture are positively associated with employees’ job involvement. This study contributes for advancing the TQM research literature to a better understanding of the association between TQM practices and employees’ job involvement within Nepalese manufacturing industry.Pravaha Vol. 24, No. 1, 2018, Page: 18-30